PERANCANGAN MEDIA PEMBELAJARAN DENGAN APLIKASI PREZI - Dian Cahyadi; Irfan Arifin; Nurabdiansyah Nurabdiansyah (Universitas Negeri makassar, 2018)
The overall objective of the Application of Science, Technology and the Arts to the public through Learning Media Design with Applications Prezi is the School Teachers SMA Negeri 5 Makassar in general, can design media with attention to the following criteria; 1) The accuracy with teaching purposes. 2) The teaching materials are the facts, principles and easy to understand. 3) Media easily obtained at least easily made by teachers and financing affordable and easy to use. 4) The existence of teachers' skills in using it. And 5) Available time to use it.The problem-solving method is to make the activities in the form of Application Workshop for Science, Technology and the Arts to the public through Learning Media Design with Applications Prezi, the material of which include; 1) Material lecture about the design of instructional media. 2) The practice of making learning media by using Prezi app offline and online with direct guidance. 3) Discussion and Q of discussing technical issues of instructional media design and application.This activity resulted in an increase in knowledge, in designing learning media effects and the ability to create compelling presentations with less using Prezi application. Related results of the workshop, the school management is very keen to work together as partners in the next time that the objectives to be achieved in realizing the vision and mission of the school can be done well.